2012
DOI: 10.1021/es303086c
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Global-Scale As, Mo, Sb, and Tl Atmospheric Pollution in the Antarctic Snow

Abstract: We report the first comprehensive and reliable time series for As, Mo, Sb, and Tl in the snowpack from Dome Fuji in the central East Antarctic Plateau. Our results show significant enrichment of these elements due to either anthropogenic activities or large volcanic eruptions during the past 50 years. With respect to the values reported from 1960 to 1964, we observed the maximum increases in crustal enrichment factors (EFs) for As (a factor of ~15), Mo (~4), Sb (~4), and Tl (~2) during the period between the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…S2); in fact, EFc is among or the highest in the entire ice core record for Ag (7), As (1.5), Bi (2), Cd (30), Cr (8), Cu (20), Mo (800), Pb (5), and Sb (3). In Antarctica, a new phase of concentration enhancements for Ag (7 times), Bi (10 times), Cr (2-4 times) after the mid 1940s (38), Pb (3 times) after A.D. 1950 (7), As (5 times), Mo (2 times), and Sb (3 times) after A.D. 1970 (39) are temporally synchronous with the corresponding increments in the Quelccaya ice core record and consistent with an influence of South American anthropogenic emissions on Antarctica during the 20th century (see, for example, Pb in Fig. 4).…”
Section: Twentieth Century Atmospheric Pollutionmentioning
confidence: 99%
“…S2); in fact, EFc is among or the highest in the entire ice core record for Ag (7), As (1.5), Bi (2), Cd (30), Cr (8), Cu (20), Mo (800), Pb (5), and Sb (3). In Antarctica, a new phase of concentration enhancements for Ag (7 times), Bi (10 times), Cr (2-4 times) after the mid 1940s (38), Pb (3 times) after A.D. 1950 (7), As (5 times), Mo (2 times), and Sb (3 times) after A.D. 1970 (39) are temporally synchronous with the corresponding increments in the Quelccaya ice core record and consistent with an influence of South American anthropogenic emissions on Antarctica during the 20th century (see, for example, Pb in Fig. 4).…”
Section: Twentieth Century Atmospheric Pollutionmentioning
confidence: 99%
“…As a consequence of Sb mining, smelting, industrial processing and waste disposal, severe enrichments with Sb have been reported in rivers, estuaries, atmospheric aerosols, soils, peat bogs, alpine and polar snow and ice (Byrd 1990;Shotyk et al 1996Shotyk et al , 2004Shotyk et al , 2005Filella et al 2002a;Cloy et al 2005;Krachler et al 2005;He et al 2012;Hiller et al 2012;Hong et al 2012). Freshwater systems are particularly affected by Sb contamination as reflected by the classification of Sb for nearly four decades among pollutants of priority interest in waters by the Environmental Protection Agency of the United States and the European Union (USEPA 1984;CEC 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Ikegawa et al, 1999;Dahe et al, 1999;Grotti et al, 2011;Thamban and Thakur, 2013). In addition, the analysis of samples collected from snow pits (Boutron and Patterson, 1983;Planchon et al, 2002a,b;Hong et al, 2002;Hur et al, 2007;Fortner et al, 2011;Hong et al, 2012) provided important time-series or seasonal patterns of trace metal deposition to the snow.…”
Section: Introductionmentioning
confidence: 99%